The role of vowel perceptual cues in compensatory responses to perturbations of speech auditory feedback - Reilly, Kevin J. (Acoustical Society of America, 2013)
The perturbation of acoustic features in a speaker's auditory feedback elicits rapid compensatory responses that demonstrate the importance of auditory feedback for control of speech output. The current study investigated whether responses to a perturbation of speech auditory feedback vary depending on the importance of the perturbed feature to perception of the vowel being produced. Auditory feedback of speakers' first formant frequency (F1) was shifted upward by 130 mels in randomly selected trials during the speakers' production of consonant-vowel-consonant words containing either the vowel /Λ/ or the vowel /ɝ/. Although these vowels exhibit comparable F1 frequencies, the contribution of F1 to perception of /Λ/ is greater than its contribution to perception of /ɝ/. Compensation to the F1 perturbation was observed during production of both vowels, but compensatory responses during /Λ/ occurred at significantly shorter latencies and exhibited significantly larger magnitudes than compensatory responses during /ɝ/. The finding that perturbation of vowel F1 during /Λ/ and /ɝ/ yielded compensatory differences that mirrored the contributions of F1 to perception of these vowels indicates that some portion of feedback control is weighted toward monitoring and preservation of acoustic cues for speech perception.